Book review: The Transition by Uroš Šuvaković - An arrow into the heart of platitudes - Bratina, Boris R. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The Transition by Uroš Šuvaković brings a serious and yet refreshing analysis of the transition, primarly in Serbia and Eastern Europe, but the author’s focus also includes the Third World and, moreover, Western Europe, thus providing a complex and comprehensive analysis of the mentioned political and sociological phaenomenon. Unlike others, Šuvaković exposes the true nature of the process of transition, indicating its ultimate cause (the interests, primarely economic, of the U. S.), as well as its final aim: the poverty of the states undergone such a process. Likewise, the author investigates the role of media in transition and brings new, until now unpublished data on Albanian crimes on Kosovo and Metohija in the period 1991–2013 into light.